Mobilizing governments and society to combat obesity: Reflections on how data from the WHO European Childhood Obesity Surveillance Initiative are helping to drive policy progress. (10th August 2021) - Breda, João; Farrugia Sant'Angelo, Victoria; Duleva, Vesselka; Galeone, Daniela; Heinen, Mirjam M.; Kelleher, Cecily C.; Menzano, Maria Teresa; Musić Milanović, Sanja; Mitchell, Lachlan; Pudule, Iveta; Rito, Ana Isabel; Shengelia, Lela; et al.
Summary: To meet the need for regular and reliable data on the prevalence of overweight and obesity among children in Europe, the World Health Organization (WHO) European Childhood Obesity Surveillance Initiative (COSI) was established in 2007. The resulting robust surveillance system has improved understanding of the public health challenge of childhood overweight and obesity in the WHO European Region. For the past decade, data from COSI have helped to inform and drive policy action on nutrition and physical activity in the region. This paper describes illustrative examples of how COSI data have fed into national and international policy, but the real scope of COSI's impact is likely to be much broader. In some countries, there are signs that policy responses to COSI data have helped halt the rise in childhood obesity. As the countries of the WHO European Region commit to pursuing United Action for Better Health in Europe in WHO's new European Programme of Work, COSI provides an excellent example of such united action in practice. Further collaborative action will be key to tackling this major public health challenge which affects children throughout the region.